Trace Metals in Residual Soil from the Oil Fields in Basrah Governorate, Iraq - Ahmed, Fatima J.; Alkafaji, Ayad H. D.; Al-Saad, Hamid T. (Mesopotamian Journal of Marine Sciences, 2025)
This research investigates the levels of trace metals in residual soil samples collected from eleven locations within the oil fields of Basrah Governorate, Iraq (Seba, Safwan, Majnoon, Ratawi, Bergezia, West Qurna 2, West Qurna 1, Shuaaba, South Rumaila, North Rumaila, and Al Zubair). The primary objective is to assess soil contamination caused by oil extraction activities, using advanced analytical techniques to evaluate heavy metal concentrations and their environmental impact. The measures of trace metals were done by Inconductivity Coupled Plasma (ICP). Metals analyzed include Zn, Cd, Mn, Pb, Fe, Cu and Cr. The study used indicators like Contamination Factor (CF), Enrichment Factor (EF), Geo-Accumulation Index (Igeo), and Pollution Load Index (PLI) to assess the contamination levels. The concentrations of Zn were at their lowest 10.765 ug/g dry weight in South Rumaila field and the highest 60.694 ug/g dry weight in Safwan field. The concentrations of Cd were at their lowest 0.304 ug/g dry weight in Shuaaba field and the highest 1.646 ug/g dry weight in West Qurna 1 field. The concentrations of Mn were at their lowest 71.847ug/g dry weight in Majnoon field and highest 396.628ug/g dry weight in West Qurna 1 field. The concentrations of Pb was lowest 0.480 ug/g dry weight in South Rumaila field and highest 39.288 ug/g dry weight in West Qurna 2 field. The concentrations of Fe was lowest 3372.278ug/g dry weight in South Rumaila field and highest 9279.445 ug/g dry weight in West Qurna 1 field. The concentrations of Cu was lowest 5.272 ug/g dry weight in South Rumaila field and highest 304.929 ug/g dry weight in West Qurna 1 field. The concentrations of Cr was lowest 18.368 ug/g dry weight in Al-Zubair field and highest 76.347ug/g dry weight in West Qurna 1 field. The results showed that Cadmium (Cd) and Copper (Cu) Showed the highest contamination levels, particularly in "West Qurna 1" and "Safwan," indicating significant industrial influence. Lead (Pb) and Zinc (Zn) Moderate contamination was observed in fields like "Safwan" and "West Qurna 2," while other sites showed lower levels. Iron (Fe), Manganese (Mn), and Chromium (Cr) Found within natural thresholds, with minimal contamination across most locations. Pollution Load Index (PLI) Most fields had PLI < 1, indicating low overall pollution, except "West Qurna 1," where PLI > 1 indicates significant contamination..